Keharmonisan Rumah Tangga Dengan Pasangan Pengidap Skizofrenia Dalam Perspektif Hukum Keluarga Islam - Anggi Maulana, Ahmad; Liyorba Indra, Gandhi; Fitri, Remeiliza (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the marital harmony of married couples where one party suffers from schizophrenia from the perspective of Islamic family law based on the Compilation of Islamic Law (KHI). The research is juridical-normative with a descriptive-analytical approach. Data sources were obtained through a literature review of the Quran, Hadith, KHI, Religious Court decisions, and fiqh munakahat literature. The results show that marital status is determined by the time the schizophrenia disorder appears. If the disorder is present before the marriage contract and causes a lack of legal awareness and competence, then the contract is null and void. Conversely, if it appears after the contract, the marriage remains valid. Healthy couples have the right to maintain the marriage or file for divorce through the Religious Court if schizophrenia causes major harm, as regulated in Article 116 letter e of the KHI. However, the main priority is maintaining harmony through regular medication, therapy, an attitude of mu'asyarah bil ma'ruf, and family support without stigma. Only if all efforts fail and the harm remains significant is the door to divorce opened as a humane Islamic solution, in accordance with the principle of